Physics learning based on the use of concept maps (2021)
Concept maps are graphic learning tools that allow teachers and students to organize, represent knowledge, and visualize the relationships between concepts to promote understanding of physics. This study describes an innovative experience based on the development of concept maps with the aim of analyzing the perception of students in a teacher training program in natural sciences and environmental education at a public university in Colombia. The research subjects were 24 students studying basic physics who used concept maps for learning, and the data were analyzed quantitatively using a non-experimental design. The results show that the trainee teachers learned to elaborate concept maps, valuing very positively their educational applications to improve learning. It is concluded that concept mapping can be used to increase students' understanding and motivation which should help to improve their academic performance.